2016
DOI: 10.1186/s12872-016-0271-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital delay in patients with first time myocardial infarction: an observational study in a northern Swedish population

Abstract: BackgroundIn myocardial infarction (MI), pre-hospital delay is associated with increased mortality and decreased possibility of revascularisation. We assessed pre-hospital delay in patients with first time MI in a northern Swedish population and identified determinants of a pre-hospital delay ≥ 2 h.MethodsA total of 89 women (mean age 72.6 years) and 176 men (mean age 65.8 years) from a secondary prevention study were enrolled in an observational study after first time MI between November 2009 and March 2012. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
27
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 57 publications
(74 reference statements)
18
27
0
6
Order By: Relevance
“…Similar finding is present in a previous studies where patients claimed longer distance of primary care center for late presentation (22,24,28). However the mode of transport (ambulance or general vehicle) was not associated with delayed hospital presentation in our study, though a study showed that patients who used private ambulance had shorter delay compared to those who used public ambulance or other transport (26).…”
Section: Pre-hospital Delaysupporting
confidence: 91%
See 1 more Smart Citation
“…Similar finding is present in a previous studies where patients claimed longer distance of primary care center for late presentation (22,24,28). However the mode of transport (ambulance or general vehicle) was not associated with delayed hospital presentation in our study, though a study showed that patients who used private ambulance had shorter delay compared to those who used public ambulance or other transport (26).…”
Section: Pre-hospital Delaysupporting
confidence: 91%
“…Older age is a widely reported risk factor of prolong pre-hospital delay (16,18,21). No significant sex difference were found in case of pre-hospital delay in this study, which is consistent with other studies from both developed and developing countries including the Bangladeshi one (10,16,(22)(23)(24). However, some other studies identified female sex as significant predictors of prolonged pre-hospital delay (12,25).…”
Section: Pre-hospital Delaysupporting
confidence: 89%
“…This understanding provides explanations for the delay to reach the hospital and points towards actions that can reduce this delay. (19) It is known that cognitive and emotional factors (interpretations, thoughts and actions in view of infarction symptoms) are associated with the delayed decision to seek care. (20) Educational activities by nurses should focus on these factors in order to optimize the search for care.…”
Section: Discussionmentioning
confidence: 99%
“…Tokias pačias išvadas galima padaryti ir apie mūsų tyrime identifikuotą rizikos veiksnį -simptomų pasireiš-kimą naktį, jis studijų buvo tiek patvirtintas [19], tiek paneigtas [20]. Kalbant apie kitus tyrime nustatytus rizikos veiksnius -gyvenimą kaime (didesnis atstumas iki gydymo įstaigos), simptomų tapatinimą su kita liga, tai daugelio studijų identifikuoti faktoriai, lemiantys vėlesnį medicinos pagalbos suteikimo laiką [10,12]. Tyrimuose nagrinėjami ir kiti galimi rizikos veiksniai: arterinė hipertenzija, cukrinis diabetas, rūkymas, krūtinės angina, buvęs miokardo infarktas, prieš tai atlikta koronarinė revaskuliarizacija ar širdies šuntavimo operacija, tačiau rezultatai dviprasmiški [18,21].…”
Section: Gs -Galimybių Santykis; Pi -Pasikliautinasis Intervalas; MI unclassified